ISLAM AND THE MORAL ECONOMY: THE CHALLENGE OF CAPITALISM - Sumiyana . (Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
This is a book review on Islam and the moral economy that highlights the challenge of capitalism.